Additive Manufacturing Approaches toward the Fabrication of Biomaterials. Issue 7 (1st February 2022) - Müller, Florence J.; Fenton, Owen S.
Abstract: The fabrication of biomaterials represents one methodology toward the creation of next generation therapies including organ and tissue replacements, drug delivery systems, and advanced pharmaceutical constructs. Overcoming challenges associated with their customization and personalization remains an area of active research. In this review, advances in the additive manufacture of biomaterials are highlighted. Specifically, topics including construct modeling, bioink selection, deposition strategy selection, and printed construct characterization are discussed. In exploring these areas, the aim of this review is to provide an overview of the biomaterials additive manufacturing process while also highlighting its application toward the betterment of human health. Abstract : Additive manufacturing plays a central role in the fabrication of personalized biomaterials for the study, prevention, and treatment of disease. In this review, key principles and advances associated with the additive manufacturing process are detailed. Topics including construct modeling, ink selection, deposition strategy, and characterization are included to highlight fundamentals and advances in the biomaterials additive manufacturing research space.